The Epistemology of Religious Experience - Webb, Mark (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue of Religions focuses on the epistemology of religious experience. The overall driving question is the question as to what evidential force religious experiences have. This discussion involves several subtopics, including the following: (1) In what ways is religious experience like other kinds of experience? (2) To what extent does religious experience influence religious doctrine, and to what extent is it influenced by it? (3) What are the implications of religious diversity/disagreement for claims of religious experience? (4) How, if in any way, has the cognitive science of religion shed light on these issues? This issue approaches these questions from a variety of religious traditions, with input from a variety of academic disciplines. The result is a collection of high-quality papers that can inform further research in a variety of academic fields.